Trançados da(s) "infância(s) boa(s)" : as con-vivências nas naturezas das ocupações ao leste-sul de João Pessoa (PB) - Mendonça, Karla Jeniffer Rodrigues de (2024)
This multi-narrative thesis moves from the notion “good childhood”, (a) collected in the investigative process, during and after the Covid-19 pandemic (2020-2022) (virtually and in person) by the braided people of the following locations: “ community” Portal do Sol, Penha, Jacarapé and Aratu. In a methodologically ethnocartographic way, within the compasses and impasses of qualitative research and a microsociological approach, it weaves a dialogue provoked by the contradictions and confluences of living in a context of territorial occupations, subjugated as scarce places by social, economic, political, cultural capital and social, that is, “behind” urban “development” and what is meant by “city”. In this work, narrative vignettes are presented about the plots of children's coexistence with the women who “raise” them in the nature of the inhabited place, permeated by income poverty and other multidimensional limits to existence. Therefore, seeking to reveal how the notion of “good childhood” (dis)harmonizes with the hegemonic notions of “living well”, “well-being” and “good life” in/for childhood(s), it is that this thesis is found in the movement of survivals linked to experiences where “it’s all family” and points to “creating” as an inter, intra and co-generational practice braided in a complex way into an infrapolitics, conditioned by dispositions and social markers (age, gender, class and race) confluent with the conditions of (r)existences in childhood. In this sense, analyzing the (non) capitalist-centric economies entangled with everyday life, it is pointed out how the “struggles” and “forces” flow against the impoverishment of practices, in satisfying needs and in the financial-symbolic support engaged, invested and faced by leaders. females in the domestic environment in coalition with childhood. As soon as the meanings of living well during childhood, linked to the affections between “entities”, are woven into an ecology of actions that emphasize recognition and redistribution centered on children through the intimacies of everyday life, which enable provision, protection and participation in/beyond the domestic environment. It is in this awakening that this thesis finds, in the compositions of “otherities” in dialogue with “communities”, the light of (dis)contentment in coexistence with the natures of the place occupied, constructed and strategically created in expansive, limited and adaptive with humans and others than humans. Thus, living well in childhood is rooted in organically occupying a place with your affections.